Additionality from Payments for Environmental Services with Technology Diffusion - Pates, Nicholas J.; Hendricks, Nathan P. (My University, 2019)
Because payments for environmental services (PES) often subsidize practices that offer latent private benefits, there are concerns that PES programs may provide little additional environmental benefits. Previous literature has framed the problem of non-additionality as an adverse selection problem. We develop a model where moral hazard can also arise because some agents delay adoption due to the incentive of potentially receiving a payment in the future. Moral hazard arises when agents have expectations of potential future subsidies, the technology naturally diffuses without a policy, and a subsidy is only available if the agent has not previously adopted the technology. We develop a conceptual model to illustrate the moral hazard incentive and conduct numerical simulations to understand the impact of policy parameters on aggregate outcomes. Numerical simulations illustrate that moral hazard creates a non-monotonic relationship between policy parameters—such as the subsidy and budget levels—and the net change in adoption induced by the program because some agents delay adoption. We also find that the cost-effectiveness of the policy is smaller when the policy is introduced during periods of rapid technology adoption.
Keywords: Payments for environmental services; Technology diffusion; Additionality